Hypokalemic periodic paralysis as the first sign of thyrotoxicosis- a rare case report from Somalia - Hawa Nuradin Mohamed; Abdi Karim Ahmed Ghedi; Sevgi Ozturk; Mohamed Osman Omar Jeele; Ahmed Muhammad Bashir (Thyroid Research, 2023)
Abstract Background Thyrotoxic hypokalemic periodic paralysis (THPP) is a rare complication of hyperthyroidism characterized by thyrotoxicosis, hypokalemia, and paralysis. It is the most common form of acquired periodic paralysis. THPP is precipitated by strenuous exercise, a high carbohydrate diet, stress, infection, alcohol, albuterol, and corticosteroid therapy. It is most common in Asian men with hyperthyroidism and exceptionally rare in black people. Case Presentation A 29-year-old man was admitted to the emergency department in Somalia with a sudden onset of paralysis after a high carbohydrate meal. Laboratory investigations showed low serum potassium 1.8 mEq/l (3.5–4.5), and biochemical thyrotoxicosis with TSH 0.006 miu/l (0.35–5.1), total T3 3.2 ng/ml (0.9–2.8) and total T4 13.5 ng/ml (0.6–1.2). He was successfully treated with potassium chloride infusion and an antithyroid drug, methimazole. Conclusion To prevent life-threatening cardiac and respiratory complications, it is critical to consider and diagnose THPP early, even in populations where the condition is rare.